ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA PEGAWAI MENGGUNAKAN PARTIAL LEAST SQUARE - PURBA, PRISCELLA; GANDHIADI, G.K.; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 13 No 1 (2024), 2024)
Partial least squares (PLS) is a powerful analytical technique that may be utilised across all data scales, without the need for numerous assumptions and without the requirement of a large sample size. In this study, the PLS method was utilized to determine the elements influencing the performance of employees of PT Pegadaian (Persero) Medan Region I office. The elements employed in this study are: leadership, work environment, discipline, remuneration and work motivation. The results showed that work motivation has a positive and significant effect on employee performance with an effect of 0.733. Factors that affect employee performance at PT Pegadaian (Persero) Medan Region I Office, namely: work motivation, remuneration, discipline and work environment.